2019
DOI: 10.1111/ene.14053
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of the additional benefit of plexus magnetic resonance imaging in the diagnosis of chronic inflammatory demyelinating polyneuropathy

Abstract: Background and purpose Hypertrophy/signal hyperintensity and/or gadolinium enhancement of plexus structures on magnetic resonance imaging (MRI) are observed in two‐thirds of cases of typical chronic inflammatory demyelinating polyneuropathy (CIDP). The objective of our study was to determine the additional benefit of plexus MRI in patients referred to tertiary centers with baseline clinical and electrophysiological characteristics suggestive of typical or atypical CIDP. Methods A total of 28 consecutive patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 28 publications
1
16
1
3
Order By: Relevance
“…Sensitivity levels of quantitative assessment of brachial plexus MRI were lower than those reported in qualitative studies [23,24]. This may be explained by some inclusion bias in earlier studies, as shown by another recent prospective cohort study that also reported a relatively low sensitivity of qualitative brachial and lumbosacral plexus MRI in patients with suspected CIDP [21]. Importantly, test-retest reliability for quantitative measurements was good, which is supported by data from another recent study [23].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Sensitivity levels of quantitative assessment of brachial plexus MRI were lower than those reported in qualitative studies [23,24]. This may be explained by some inclusion bias in earlier studies, as shown by another recent prospective cohort study that also reported a relatively low sensitivity of qualitative brachial and lumbosacral plexus MRI in patients with suspected CIDP [21]. Importantly, test-retest reliability for quantitative measurements was good, which is supported by data from another recent study [23].…”
Section: Discussionmentioning
confidence: 67%
“…MRI is part of the current diagnostic criteria for CIDP and MMN and is recommended in particular for the identification of elusive cases, i.e. those without clear NCS abnormalities [1,2,[18][19][20][21]. This is based on several MRI studies that showed cervical nerve root thickening and increased signal intensity on brachial plexus MRI in a subgroup of patients with chronic inflammatory neuropathies [7,20].…”
Section: Discussionmentioning
confidence: 99%
“…Магнитно-резонансная томография (МРТ) служит вспомогательным инструментом в диагностике ХВДП, а характерные нейровизуализационные изменения входят в поддерживающие критерии EFNS/PNS (2010) [1]. При классической ХВДП описано повышение сигнала и/или гипертрофия стволов сплетений или корешков на Т2-взвешенном изображении с накоплением контрастного вещества или без такового, что, по разным данным, встречается у 44-88% пациентов с ХВДП [18][19][20]. Такой разброс может быть обусловлен различием дизайна и протоколов исследования, малой выборкой пациентов [3].…”
Section: классификация и краткое описание форм хронической воспалителunclassified
“…Такой разброс может быть обусловлен различием дизайна и протоколов исследования, малой выборкой пациентов [3]. Большинство исследований не показало достоверной связи между отсутствием или наличием изменений по данным МРТ, а также их характером с длительностью, тяжестью заболевания и проводимой терапией [18]. МРТполезный дополнительный метод диагностики ХВДП, особенно в случае несоответствия критериям EFNS/PNS (2010), однако он отличается высокой стоимостью, наличием требований к техническому оснащению и специальной подготовке врача-радиолога [3].…”
Section: классификация и краткое описание форм хронической воспалителunclassified
“…Это связано с тем, что ХВДП, как и большинство аутоиммунных нервно-мышечных заболеваний, не имеет однозначных маркеров аутоиммунного процесса, а биопсия периферического нерва [2,5,26] пациентам не была проведена в связи с описанными выше причинами. Нами также не проводились в представленной выборке такие исследования, как люмбальная пункция, магнитно-резонансная томография сплетений с контрастным усилением, исследование уровня антител к ганглиозидам периферических нервов, так как отсутствие белка в ликворе не исключает ХВДП [26,27], визуализация сплетений при магнитно-резонансной томографии в 40-60 % случаев не показывает изменений при дизиммунных нейропатиях [28] и особенно малоинформативна при атипичных формах, а антитела к ганглиозидам имеют низкую диагностическую значимость и в диагностике ХВДП не применяются вовсе [5,6]. В определенной степени в пользу дизиммунного генеза у наших Оригинальные исследования больных мог свидетельствовать положительный ответ на патогенетическую терапию [5,29].…”
Section: оригинальные исследованияunclassified